2003
DOI: 10.1038/sj.onc.1206723
|View full text |Cite
|
Sign up to set email alerts
|

A porphobilinogen deaminase (PBGD) Ran-binding protein interaction is implicated in nuclear trafficking of PBGD in differentiating glioma cells

Abstract: Porphobilinogen deaminase (PBGD) is a rate-limiting enzyme of the heme biosynthesis pathway, whose level is elevated in various human tumors. PBGD was observed in both nuclear and cytoplasmic fractions of C6 glioma cells by immunostaining. During mitosis, chromatids were intensely stained for PBGD in comparison to the interphase chromatin. Using the yeast two-hybrid system, we identified RanBPM, the nuclear Ran-binding protein, as an interacting partner of PBGD. During butyrateinduced differentiation of C6, bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 45 publications
0
14
0
2
Order By: Relevance
“…Decreased expression of PBGD mRNA in AD may be unrelated to heme biosynthesis. A “moonlighting” function for PBGD in the cell nucleus, which in glioma cells may be linked to tumorigenesis and cell cycle activity, has been reported [11, 12]. Moreover, 50% reduction in PBGD mRNA expression by itself may not significantly affect cerebral heme synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of PBGD mRNA in AD may be unrelated to heme biosynthesis. A “moonlighting” function for PBGD in the cell nucleus, which in glioma cells may be linked to tumorigenesis and cell cycle activity, has been reported [11, 12]. Moreover, 50% reduction in PBGD mRNA expression by itself may not significantly affect cerebral heme synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Our present independent methods of immunolabelling and GFPtagging reveal dual localisations of PBGD in B16 melanoma cells, one cytosolic and the other nuclear. Recently, we have shown interaction between PBGD and a nuclear protein Ran-binding protein (Greenbaum et al, 2003). These findings are indicative of a possible dual function of PBGD, one enzymatic in the cytoplasmic heme pathway and an unknown role in the nucleus.…”
Section: Discussionmentioning
confidence: 73%
“…PBG-D is a key enzyme in heme biosyntesis and it is expressed as two isoforms, a housekeeping isoform present in all cell types and a second isoform expressed only in erythroid cells (37). Greenbaum et al (38) showed that overexpression of the human housekeeping PGB-D has been found to induce C6 glioma cell differentiation toward astrocytes. Ickowicz Schwartz et al (22) demonstrated that stimulation with HMBA induced melanocytic differentiation accompained by a prominent increase in total PBGD as well as an increase of PpIX.…”
Section: Discussionmentioning
confidence: 99%